Evaluating an Information Campaign about Rural Development Policies in FYR Macedonia - Huber, Martin; Kotevska, Ana; Stojcheska, Aleksandra Martinovska; Solovyeva, Anna (Cambridge University Press (CUP), 2018)
This study investigates the effects of a local information campaign on farmers’ interest in a rural development programme (RDP) in the former Yugoslav Republic of Macedonia. The results suggest that while our intervention succeeded in informing farmers, it had a negative, albeit only marginally significant, effect on the reported possibility of using future RDP support. This puzzling result can be attributed to increased awareness of administrative burden associated with RDP participation. An additional heterogeneity analysis suggests the negative effect is driven by unprofitable farmers who are averse to any administrative encumbrance, for whom upfront cofinancing of an RDP is untenable.
Keywords: field experiment, FYR Macedonia, information provision, rural development, treatment effects